2020
DOI: 10.33689/spormetre.672742
|View full text |Cite
|
Sign up to set email alerts
|

Amatör Futbol Li̇gi̇nde Ev Sahi̇bi̇ Olma Avantaji: Türki̇ye Futbol Bölgesel Amatör Li̇gi̇ Örneği̇

Abstract: Sonuç olarak BAL Liginde 5 sezonun ev sahibi ortalamasının %58,24 olduğu ve bununda literatürdeki çalışmalarla benzerlik taşıdığı gözlemlenmiştir. Bölgesel Amatör ligde Ev sahibi olma avantajı ortalamasının %50 den yüksek olması literatürdeki birçok çalışma ile benzerlik taşımaktadır. Futbolda başarılı bir sezon geçirebilmek için sadece ev sahibi olarak puan kazanmanın yeterli olmayacağı, daha iyi bir lig sıralaması için deplasmanda kazanılan puanların da çok önemli bir kriter olduğu söylenebilir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Scoppa [18] showed that the number of fouls, yellow cards, and red cards decreased during home games without an audience Scoppa [18]. In Turkey Regional Amateur League, home advantage was observed in more than 50% of the matches in the last five years [19]. In the abovementioned study, home GF per game was 1.61, and away GF was 1.20.…”
Section: Discussionmentioning
confidence: 71%
“…Scoppa [18] showed that the number of fouls, yellow cards, and red cards decreased during home games without an audience Scoppa [18]. In Turkey Regional Amateur League, home advantage was observed in more than 50% of the matches in the last five years [19]. In the abovementioned study, home GF per game was 1.61, and away GF was 1.20.…”
Section: Discussionmentioning
confidence: 71%